Improved out-of-plane properties through alternative print path and in-layer heating - Ole S. Nesheim; Anni Cao; Lisa Ducarouge; Christer W. Elverum (Virtual and Physical Prototyping, 2025)
Anisotropy in fused filament fabrication of short fibre-reinforced polymer composites is mainly caused by uniform fibre direction and poor layer bonding. This study aims to improve the out-of-plane mechanical performance of carbon fiber-reinforced polyamide 6 parts by combining in-layer infrared postheating and a custom lifting toolpath designed to orient fibres in the out-of-plane direction. Single-walled samples manufactured with the lifting (L) and conventional toolpath (C) were printed at 1.2 and 3mm/s. Mechanical testing revealed an increased tensile modulus of 11.5% solely from the L toolpath. Compared to benchmark samples, an increase of 118.9% and 207.4% in ultimate tensile strength (UTS) and tensile modulus, respectively, was observed. Scanning electron microscope (SEM) images and crystallinity measurements indicated that while out-of-plane fibre rotation occurred within individual layers, it did not sufficiently bridge stacked layers to significantly impact UTS. The primary increase in UTS was thus attributed to enhanced matrix bonding due to postheating, while the L toolpath effectively increased the tensile modulus. Based on matrix structure variations observed in the SEM images, we hypothesize that the initially porous structure solidifying after material deposition can be effectively eliminated by postheating, resulting in increased interlayer contact area, ultimately enhancing UTS.